Ethics and sustainable development - Álvarez Astengo, Carlos R. (2019)
The Sustainable Development Goals (SDG) of the United Nations (UN) are intended to create a set of global objectives related to environmental, political and economic challenges, addressingextreme poverty and hunger, among others, as development priorities. The SDG’s are an urgent call for the world to make the transition to a more sustainable path.About the sustainable or sustainable development can be said in general lines that is where the development of the present generation meets their needs without limiting future generations so that they can also meet their needs.In the present work, a comprehensive evaluation of sustainable development processes is developed, from a state perspective and from the perspective of international organizations such as the PNUD. In this way, it is a deep inquiry about bioethics patterns.